Emulsion Liquid Membrane Extraction of Turquoise Blue Reactive Dye–Study on Membrane Breakage and Swelling - Othman, N.; Zailani, S. N.; Mili, N. (Journal of Applied Membrane Science & Technology, 2017)
Reactive dyes are the principal dyes used in batik industry in Malaysia. From the environmental point of view the dyes should be removed from wastewater because they are toxic in nature. Therefore, the removal and recovery of dyes from batik industry wastewater is absolute necessity in order to save raw materials and to protect environment from hazardous compounds. An experiment was carried out using emulsion liquid membrane (ELM) process in batch system to study the extraction behaviour of Turquoise Blue which is commonly used in batik industry. Several parameters have been studied such as carrier and surfactant/emulsifier concentrations, stripping agent and extraction time. The liquid membrane was formulated using kerosene as diluent, SPAN 80 as emulsifier and tri-dodecylamine (TDA) as a carrier. Hydrodynamic condition to generate extraction process was at 1:3 treat ratio and 250 rpm stirring speed for 10 minutes while the emulsification was done at 12000 rpm for 5 minutes using homogenizer. The result obtained shows that, more than 70% of Turquoise Blue was extracted at favourable condition of 0.07 M TDA, 7% (w/v) SPAN 80 and 0.5 M Thiourea in 1 M NaOH.